THE IMPACT OF HUMAN RESOURCES, SOCIAL CAPITAL AND ECONOMIC INFRASTRUCTURE ON ECONOMIC GROWTH: EVIDENCE IN INDONESIA - Garaika , Helisia Margahana , Citrawati Jatiningrum (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study concerns to investigate the impact of human resources, economic infrastructure, and social capital respectively on economic growth in East Lampung Regency. Sample study conducted in 24 districts and using data panel analysis. The findings of this study reveal that there is an effect between the number of productive age, road infrastructure and electricity consumption on economic growth while evidence also shows the consumption of clean water by the population has no effect on economic growth in East Lampung. The results of this research can be input for policymaking which the local government to assist in decision-making in improving the community economy in East Lampung Regency. Human resource optimization and efforts to improve infrastructure and social capital empowerment can increase regional economic growth, thus affecting the efficiency and smoothness of economic activities in other sectors